GAMBARAN KARAKTERISTIK PENDERITA ATONIA UTERI DI RUMAH SAKIT UMUM DAERAH DR. PIRNGADI MEDAN - Alex Lumbanraja; Kamajaya Kamajaya (Majalah Ilmiah METHODA, 2018)
Uterine atony is a postpartum condition in which the uterus does not contract and retract so that the blood coming out of the placenta becomes uncontrolled. The failure of the uterus to contract after giving birth is often the cause of labor bleeding. The incidence of uterine atony is 50-60% from the 5-15% rate of postpartum events. The purpose of this study was to determine the characteristics of uterine atony patients. This study used a descriptive research method with a cross-sectional design. This research was conducted in April-May 2016 at Dr. Pirngadi General Hospital Medan. By using the total sampling method, with a sample of 47 patients who had met the sampling criteria. Data was collected by taking data from medical records from 2010-2013, then processing and analyzing data. This study obtained the highest proportion of the age group 36-40 years 30%, 94% high school education, housewife work 94%, multipara parity 64%, number of babies born single 96%, birth weight 3600-4000gr 38%, hemoglobin before labor 8-10gr / dl 74%, age tabulation with 30% parity and weight tabulation of babies born with hemoglobin before delivery 38%. In this study, it is known the frequency distribution of characteristics of uterine atony based on age, parity, the number of infants collected, birth weight, and hemoglobin before delivery at Dr. Pirngadi General Hospital Medan.